Hybrid Synergic Methodology to Prepare ALD Honey‐Comb Anatase Films. Issue 10 (10th November 2015) - Visentin, Francesca; El Habra, Naida; Favaro, Monica; Battiston, Simone; Gerbasi, Rosalba; Crociani, Laura; Galenda, Alessandro
Abstract : Macroporous inorganic structures with high surface‐to‐volume ratio have been recognized as a centre of interest in many fields. Here, attention is focused on a hybrid synergic methodology to prepare honey‐comb (HC) anatase TiO2 films with increased specific surface area. The breath figures (BFs) method is exploited to produce HC polystyrene (PS) templates and atomic layer deposition (ALD) is used to conformally cover them with a TiO2 coating. Different approaches are tested to preserve the HC‐TiO2 structure during the conversion of the hybrid organic/inorganic materials into crystalline anatase films. Best results are obtained operating with ALD at 180 °C on pre‐UV cross‐linked substrates. Abstract : A hybrid synergic methodology to prepare honey–comb (HC) anatase TiO2 films with increased specific surface area is presented. The breath figures method is used to produce HC polystyrene templates and atomic layer deposition is used to conformally cover them with a TiO2 coating. Different approaches are tested to preserve the HC‐TiO2 structure during the conversion of the hybrid organic/inorganic materials into HC‐crystalline anatase films.